2009
DOI: 10.3177/jnsv.55.22
|View full text |Cite
|
Sign up to set email alerts
|

High Casein Diet Decreases Plasma Homocysteine Concentration in Rats

Abstract: Summary Experiments were conducted to clarify the relationship between dietary protein level and plasma homocysteine concentration in rats. Male Wistar rats were fed diets differing in casein level from 5 to 50% for 14 d (Expt. 1). Plasma total homocysteine concentration was positively correlated with dietary casein level in the range of 5 to 10% but inversely correlated with dietary casein level in the range of 10 to 50%. Hepatic cystathionine ␤ -synthase (CBS) and betaine-homocysteine S -methyltransferase (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…Hence, the folate deprivation-induced hyperhomocysteinemia observed in the present study was moderate (34.1 M) and mild (26.5 M) in rats fed 10C and 20C, respectively, indicating that increasing dietary casein level led to resistance against folate deprivationinduced elevation of plasma homocysteine concentration. Consistent with this, we previously demonstrated that diets containing higher levels of casein or soybean protein did not increase but rather decreased plasma homocysteine concentrations (39,40). Furthermore, guanidinoacetic acid-induced hyperhomocysteinemia was also suppressed by raising the dietary casein level (41).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Hence, the folate deprivation-induced hyperhomocysteinemia observed in the present study was moderate (34.1 M) and mild (26.5 M) in rats fed 10C and 20C, respectively, indicating that increasing dietary casein level led to resistance against folate deprivationinduced elevation of plasma homocysteine concentration. Consistent with this, we previously demonstrated that diets containing higher levels of casein or soybean protein did not increase but rather decreased plasma homocysteine concentrations (39,40). Furthermore, guanidinoacetic acid-induced hyperhomocysteinemia was also suppressed by raising the dietary casein level (41).…”
Section: Discussionsupporting
confidence: 66%
“…It is thought that protein-unbound homocysteine is taken up and metabolized in the kidney. We previously demonstrated that renal CBS activity was increased by raising the dietary casein level (40). Hence, it is possible that clearance activity of plasma protein-unbound homocysteine is greater in rats fed 20CFD than in rats fed 10CFD.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous 253 folate-restriction studies using a rat model did not exhibit elevations in hepatic BHMT activity to 254 the extent demonstrated with this mouse model [23]. Others have reported that dietary-mediated 255 alterations in hepatic BHMT activity resulted in decreased homocysteine concentrations [45]. 256…”
mentioning
confidence: 61%
“…While results from some human (81) and rodent (82,83) studies suggest a decreased effect on homocysteine with moderate to high protein diets, other authors report a significantly positive correlation between protein intake and plasma homocysteine concentration in humans (65). In rats, higher homocysteine concentrations are exhibited in animals consuming a high versus animals fed a standard casein diet (84).…”
Section: Proteins and Amino Acidsmentioning
confidence: 99%